Profile of newborns undergoing early stimulation in a neonatal intensive care unit - Karla Camila Lima de Souza; Nataly Gurgel Campos; Francisco Fleury Uchoa Santos Júnior (Universidade de Fortaleza, 2014)
Objective: To describe the profile of newborns undergoing early stimulation in a neonatal intensive care unit, characterizing the study population according to their neonatal variables and risk factors indicative for the early stimulation treatment. Methods: Cross-sectional and analytical study, held in a reference hospital of Fortaleza, in the period from February to March 2011, with sample consisting of 116 medical records of newborns indicated for the early stimulation treatment. The following variables were analyzed: weight, sex, gestational age, Apgar score, diagnosis of Respiratory Distress Syndrome and Intracranial Hemorrhage, use of mechanical ventilation and continuous positive airway pressure (CPAP). The variables were analyzed using Microsoft Excel™ 2007 software to obtain mean and mode. Results: Among the studied variables, there was a prevalence of low birth weight, prematurity and male newborns. According to the Apgar score, scores of 1st and 5th minutes showed increasing values. Regarding the studied pathologies, the Respiratory Distress Syndrome stands out as the most prevalent, followed by Intracranial Hemorrhage. Concerning the use of mechanical ventilation, CPAP was the most frequently indicated modality, followed by mechanical ventilation. Conclusion: The profile of newborns investigated in this study, which underwent early stimulation in a neonatal intensive care, is represented by male, premature, low weight and high rate of Apgar score at 1st and 5th minutes, with prevalence of respiratory distressand increased use of CPAP. doi:http://dx.doi.org/10.5020/18061230.2013.p523